2015
DOI: 10.1103/physrevapplied.3.024001
|View full text |Cite
|
Sign up to set email alerts
|

Ejection Regimes in Picosecond Laser-Induced Forward Transfer of Metals

Abstract: Laser-induced forward transfer (LIFT) is a 3D direct-write method suitable for precision printing of various materials, including pure metals. To understand the ejection mechanism and thereby improve deposition, here we present visualizations of ejection events at high-spatial (submicrometer) and hightemporal resolutions, for picosecond LIFT of copper and gold films with a thickness 50 nm ≤ d ≤ 400 nm. For increasing fluences, these visualizations reveals the fluence threshold below which no ejection is observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 56 publications
2
42
0
Order By: Relevance
“…Only recently has the focus shifted to the impact of much smaller drops, with a radius of a few tens of micrometres, corresponding to the typical size of drops coming from, e.g., an inkjet nozzle (Basaran, Gao & Bhat 2013;Driessen et al 2013). Microdrop impact is highly relevant for many rapidly developing applications, such as immersion lithography (Keij et al 2013), extreme ultraviolet (EUV) lithography (Klein et al 2015) and 3D printing (Gibson, Rosen & Stucker 2010;Pohl et al 2015), spray painting and spray coating. Very recently it has been found that the phenomena for microdrops impacting on a solid surface are similar to those of larger (millimetre-sized) impacting drops .…”
mentioning
confidence: 99%
“…Only recently has the focus shifted to the impact of much smaller drops, with a radius of a few tens of micrometres, corresponding to the typical size of drops coming from, e.g., an inkjet nozzle (Basaran, Gao & Bhat 2013;Driessen et al 2013). Microdrop impact is highly relevant for many rapidly developing applications, such as immersion lithography (Keij et al 2013), extreme ultraviolet (EUV) lithography (Klein et al 2015) and 3D printing (Gibson, Rosen & Stucker 2010;Pohl et al 2015), spray painting and spray coating. Very recently it has been found that the phenomena for microdrops impacting on a solid surface are similar to those of larger (millimetre-sized) impacting drops .…”
mentioning
confidence: 99%
“…Other groups used thicker films [17] or longer pulse durations [76,77] to perform the transfer of liquid metal droplets from a solid film. They successfully printed conductive lines, but the thermal effects induced by the high energy deposition required to melt such thin film lead to the generation of large amount of melted debris around the printed structures.…”
Section: Lift Of Solid In Liquid Phasementioning
confidence: 99%
“…The ejection momentum is the most important factor for transferring the target material from the donor layer to the acceptor layer in LIFT34. A sacrificial layer, called the dynamic release layer, is usually applied between the carrier and the donor layer to increase the momentum during LIFT.…”
mentioning
confidence: 99%